Analisis Tingkat Kepuasan Pengguna Aplikasi Pengelolan Persediaan BMD di SMK Negeri 17 Jakarta Menggunakan Metode Service Quality - Bagus Wibisono; Goldie Gunadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze user satisfaction with the inventory management application for Regional-Owned Assets (BMD) at SMK Negeri 17 Jakarta using the SERVQUAL method. The application was implemented to enhance asset management efficiency, but challenges such as data inaccuracies and limited user skills hinder its effectiveness. The SERVQUAL method evaluates five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy, by measuring the gap between user expectations and perceptions. The findings reveal that all service quality dimensions have negative GAP values, particularly in reliability and tangibles, indicating that the application has not fully met user expectations. Therefore, improvements in system reliability, application design, and technical training are essential to optimize the use of the application for effective asset management in the school.